Ways of EFL Teachers in Developing Their Pedagogical Competences - Vivi Aulia (Universitas Hamzanwadi, 2021)
Producing EFL teachers who have the capacity in managing classroom always deal with the mastery of pedagogical competence whether in theory and practice. This study aimed at discussing EFL teachers’ views in implementing pedagogy as the way of teaching. This study was called analysis of research articles dealing with pedagogical competence. There were ten research articles as the source of data and it was documentation. The analysis data used content analysis because it attempted to apply cross-analysis to find out the main points among the research articles. The study result shows that in order to make EFL teachers manage the classroom activities, they are required to have a bunch of pedagogy knowledge such as designing material, teaching activities, evaluation, and feedback. Besides that, the mastery and literacy of technology are needed to drive EFL teachers to operate teaching-learning media in the effort to enhance learners towards technology-based learning. Using cultural ways in teaching is the way to close the students with the environment to make them easy in getting the knowledge in theory and practice.